Brazil: Roots of Popular Culture (experience of interpretations) - I. A. Malkovskaya (Ибероамериканские тетради)
The roots of Brazilian folk culture have different forms, structure and history. These roots have been formed over a long period, they have intertwined and influenced one another. Authentic cultures (Indian tribes) and «newcomers» (African and European culture) have been interacting with one another in complex socio-political realities. Together these cultures have created a vivid aesthetic image of the country. The aesthetic principle is most clearly expressed in folklore, the forms of which are diverse and multifaceted. The culture of the people is dynamic; it speaks through folklore in a variety of verbal and non-verbal languages: plastic art, music, dance, folk crafts, national costumes, works of the verbal genre (fairy tales, epics, legends, myths, etc.). Folk culture defines the identity of society, it is reflected in the high aesthetics of professional visual art, music, literature and gradually enters into mass culture and show business. Modernism, the art trend of the early 20th century, became a vivid reflection of the folk features of Brazilian culture. Over time, the tendency to rely on folk national culture has intensified, affecting all aspects of society — from mass culture to social policy. The cultural construction of society in close interaction and cooperation with the folk tradition, the consolidation and renewal of tradition ultimately determine the mentality of the nation, the stability of its existence and self-preservation. The study of Brazilian folk culture opens up new horizons for those who yearn to understand the world of diversity and the world of beauty. The coexistence in a single space of the people of many traditions and aesthetic images that do not oppose, but complement each other, inspires historical optimism which is «colored» by our experience of interpreting the culture of Brazil.